Estimation of Stature from Anthropometric Measurements of the Sternum in Nepalese Population at the Tertiary Health Care Hospital - Bista, Binamra; Thapaliya, Narad Prasad; Chaudhary, Aswani; Shrestha, Pramod Kumar; Kandel, Tulsi (Nepal Journal of Health Sciences, 2024)
Introduction: Stature estimation is crucial for identifying human remains in forensic and anthropological contexts, aiding in mass casualties, criminal investigations, and archaeological studies. Traditionally using long bones, alternative methods are necessary when these bones are unavailable or fragmented.Objectives: The main purpose of this study was to access the morphometric measurements of the study population and compare the findings between the two sexes.Method: A study of 100 medico-legal autopsies at Department of Forensic Medicine, Maharajgunj Medical Campus, Nepal investigated stature estimation from sternal lengths. During autopsies, cadaver length was measured using a steel tape. An incision was made from the suprasternal notch to the pubis, the sternum was removed, and the combined manubrium and mesosternum length was measured with sliding callipers.Results: The study included 67 male and 33 female cadavers, with a mean age of 37.46 years. The mean length of the manubrium was 43.34 ± 6.88 mm (44.58 ± 7.15 mm for males, 40.81 ± 5.59 mm for females). The mesosternum averaged 101.85 ± 15.65 mm (104.40 ± 16.68 mm for males, 96.66 ± 11.92 mm for females). The combined sternal length was 146.12 ± 16.64 mm. Body length correlated weakly but significantly with manubrium, mesosternum, and combined sternal lengths (r = 0.242, 0.206, 0.320 respectively).Conclusion: Stature estimation from sternal length is valuable for identifying mass casualty victims, with males showing greater measurements. Combined manubrium and mesosternum lengths are better stature estimators.